ANALISIS TINGKAT CEMARAN LOGAM TEMBAGA DAN TINGKAT PENDAPATAN USAHATANI SAYURAN DI KEBUN KARTAMA DAN KEBUN KOMPPOS – EM KOTA PEKANBARU - Shally Yanova; - Zulkarnaini; Sofia Anita (LPPM Universitas Muhammadiyah Riau, 2016)
The study was done in August to September 2015 and located in the Kartama Garden (PSN) on Kartama street Marpoyan Damai district area and KOMPPOS – EM garden (PSO) at the University of Riau, Pekanbaru. The purpose of this research is determining metal Cu (copper) in vegetable (mustard, convolvulus and lettuce) and soil, determining the rate of pollution metal Cu, analyzing the use of fertilizer and pesticide synthetic levels of metal Cu in a sample and analyzing the impact of agricultural income activity for farmers. Based on the research, levels of metal Cu in vegetables and soil PSN had passed of quality standard Director General POM RI namely 5,0 mg/kg and categorized polluted metal Cu. While sample vegetable KOMPPOS - EM garden (PSO) is still under environmental quality category and including contaminated. Using fertilizer and pesticide synthetic and continuing to exceed doses constantly affects levels of metal Cu in a sample of vegetables and soil significantly. Economically, PSN and PSO farming is agricultural activity that can give advantages for farmers.